Research of the processing methods and compression of graphical information - Егорова, Ирина Николаевна; Чёрненькая, Евгения Владимировна (Eastern-European Journal of Enterprise Technologies, 2012)
Web-design is a growing sector of computer graphics due to the wide spread of Internet. Graphical format for displaying web-content should provide efficient storage and organization of data exchange between different applications while maintaining visual quality. Developers are working on increasing the capacity of communication channels, browser rendering speed, increased storage, but little attention is paid to the development and improvement of image formats. Researching of the new elaborated graphics formats that use data compression algorithm with optimal image quality and minimizing the size of the data is relevant. In this article we have studied the new graphic file formats such as JPEG XR and WebP and compared them with JPEG format and represented the graphs comparing the percentage of formats compression and visual assessment of the converted images. The new formats analysis of advantages and disadvantages have been represented for the development of web-applications. The results are used to make recommendations on the feasibility of the new file formats for graphical web-content and design